Hippocampus duality: Memory and novelty detection are subserved by distinct mechanisms. Issue 4 (23rd January 2017) - Barbeau, Emmanuel J.; Chauvel, Patrick; Moulin, Christopher J.A.; Regis, Jean; Liégeois‐Chauvel, Catherine
ABSTRACT: The hippocampus plays a pivotal role both in novelty detection and in long‐term memory. The physiological mechanisms underlying these behaviors have yet to be understood in humans. We recorded intracerebral evoked potentials within the hippocampus of epileptic patients ( n = 10) during both memory and novelty detection tasks (targets in oddball tasks). We found that memory and detection tasks elicited late local field potentials in the hippocampus during the same period, but of opposite polarity (negative during novelty detection tasks, positive during memory tasks, ∼260–600 ms poststimulus onset, P < 0.05). Critically, these potentials had maximal amplitude on the same contact in the hippocampus for each patient. This pattern did not depend on the task as different types of memory and novelty detection tasks were used. It did not depend on the novelty of the stimulus or the difficulty of the task either. Two different hypotheses are discussed to account for this result: it is either due to the activation of CA1 pyramidal neurons by two different pathways such as the monosynaptic and trisynaptic entorhinal‐hippocampus pathways, or to the activation of different neuronal populations, that is, differing either functionally (e.g., novelty/familiarity neurons) or located in different regions of the hippocampus (e.g., CA1/subiculum). In either case, these activities may integrate the activity of two distinct large‐scale networks implementing externally or internally oriented, mutually exclusive, brain states. © 2017 Wiley Periodicals, Inc.